Creating Europe from the Margins Mobilities and Racism in Postcolonial Europe - Loftsdóttir, Kristín; Hipfl, Brigitte; Ponzanesi, Sandra (Taylor & Francis, 2024)
Europe; Margins; Racism; Colonialism; Migration; Boundaries; Borders; Gender; Class; Sexuality; Religion; Nationality